PENGEMBANGAN USAHA KERANG BULU MENJADI SEDIAAN ABON DI DESA PEMATANG CENGAL KABUPATEN LANGKAT - Sinaga, Lia Rosa Veronika; Tarigan, Malemta; Silalahi, Yosy Cinthya Eriwaty (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Pematang Cengal Village is located in Langkat Regency, North Sumatra, Indonesia. Because it is directly adjacent to the Palung Nipah river, the majority of the population are fishermen. Fur mussels are usually sold to clam collectors at relatively cheap prices. The purpose of this community service is to process feather clams into shredded shells so that they have a higher selling value compared to the sale of fresh shellfish. and has durable products with proper processing processes and can be simply done by the people of Pematang Cengal. When the activity was carried out, the people of Pematang Cengal were very happy with the new innovations to process shellfish into new products. So that fishermen's wives can fill their time to be more useful for their families, serving tastier and more nutritious dishes as well as shellfish products that are more durable in storage. If done simultaneously with other wives, it is hoped that it can be a business development for the community in Pematang Cengal to become one of the UMKM in Indonesia.